الاتجاه الليبرالي في التعامل مع السنة النبوية في إندونيسيا دراسة تحليلية نقدية - صالحين,زهر الفتى (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
One of the major issues that have occupied intellectual discourses in the contemporary Muslim World is pertaining to criticism of religious texts. This study seeks to examine and respond to the various criticisms of the Prophet's tradition (Sunnah) which have been launched by liberal thinkers in Indonesia. The method used in this research is both deductive and critical-analytical. The former is employed in order to collect various criticisms of Sunnah and classify them into two categories, namely, [i] those relating to the concept of Sunnah and its authority, and [ii] those pertaining to the authenticity of the Sunnah. The second method is employed in order to subject all these criticisms to penetrating analysis and critical assessment based on the established principles of hadith sciences and its methodology as well as with reference to the works of authoritative scholars in the field with a view to unearthing the roots and origins of those criticisms. This study has come to the conclusion that most if not all criticisms leveled by Indonesian liberal thinkers against the Sunnah are mere repetition of those raised by the modern Western scholars and by contemporary Muslim thinkers –Arab as well non-Arab – who came under the spell of the Orientalists. This study also uncovers the striking similarities between them in attacking the Sunnah and vilifying Islam, using methods that are neither scientific nor objective. Their flawed approach includes using arguments based on presuppositions or unproven assumptions, relying on weak opinions, suppressing the truth and distorting the facts, a bold tendency towards materialistic and empiricist interpretation, a penchant for historical-critical analysis, giving priority to context over the text in the name of public interest (maslahah) or Shari'ah objectives (maqạsid), and referring to dubious sources.